(untitled) (Journal of Eye Movement Research, 2018)
These days, eye-tracking is one of the promising technologies used in different fields. However, studies involving eye-tracking are rare in the field of endo-neurosurgery. This study aims to use this technology to promote our understanding of the effect related to computer-based instructional materials on mental workload of surgical residents. Four computer-based simulation scenarios are developed, two of them were designed as general models and the other two as simulated surgical models. During these surgical procedures, in real settings, surgical residents need to use their both hands simultaneously to control the endoscope and the operational tool in a coordinated fashion. Therefore, to shed light on the participants’ behaviors, these scenarios are performed with dominant-hand, non-dominant hand and, finally with both-hands. Twenty-three residents’ eye-movements were recorded while performing the scenarios. According to the results of this study, when performing the simulated surgical models, an increase in the participants’ mental workload was recorded when compared to the other scenarios. Accordingly, it can be concluded that the eye-movements of surgical residents can provide insights about the anticipated level of difficulty about the skill-based tasks. This information might be very critical to properly design and organize instructional materials for endo-neurosurgery, and also to better guide and evaluate the progress of trainees in computer simulation-based skill training environments.